2005
DOI: 10.1080/13638490400022212
|View full text |Cite
|
Sign up to set email alerts
|

Brace treatment during pubertal growth spurt in girls with idiopathic scoliosis (IS): A prospective trial comparing two different concepts

Abstract: The SpineCor does not change natural history of idiopathic scoliosis during the pubertal growth spurt. The use of the Chêneau brace seems to do so. Oncoming studies with the aim to test the efficiency of braces should be based on samples at immediate risk for progression (only girls with first signs of maturation but pre-menarchial).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
89
3
6

Year Published

2010
2010
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(97 citation statements)
references
References 14 publications
0
89
3
6
Order By: Relevance
“…At the final follow-up, the success rate of brace treatment in our study was 81%. In the literature, success rates and follow-up durations associated with other braces were lower than those associated with the Chêneau brace, 1,8,20,21 but the results of other published studies were not certain. The Chêneau brace resulted in a higher percentage of correction for thoracic curves at the final follow-up; however, it may not prevent curve progression effectively for double major curves.…”
Section: Discussionmentioning
confidence: 87%
“…At the final follow-up, the success rate of brace treatment in our study was 81%. In the literature, success rates and follow-up durations associated with other braces were lower than those associated with the Chêneau brace, 1,8,20,21 but the results of other published studies were not certain. The Chêneau brace resulted in a higher percentage of correction for thoracic curves at the final follow-up; however, it may not prevent curve progression effectively for double major curves.…”
Section: Discussionmentioning
confidence: 87%
“…Soft braces certainly allow for more spinal and trunk mobility; however, when applied to a moderate or severe curve, with significantrotation,evidenceislacking that the rotational component of scoliosis improves. while independent studies do not corroborate this claim 18,19 . Scoliosis is a three-dimensional deformity of the spine and trunk, sometimes leading to a drastic increase in the curvature during growth, a process known as curvature progression [1][2][3][4][5] .…”
Section: Introductionmentioning
confidence: 47%
“…Biomechanically, correction may vary according to brace type, and each brace is tolerated differently, which may affect compliance. We may also assume that bracing outcomes will differ when comparing symmetric braces to asymmetric ones [14][15][16][17][18][19][20] . One problem in the literature regarding bracing is the comparison of patient samples with different prognoses, for example varying Risser classification and/or curve magnitude.…”
Section: Introductionmentioning
confidence: 99%
“…A prospective controlled study comparing the Chêneau brace with SpineCor has clearly shown the superiority of the Chêneau brace in a sample of patients at actual risk for being progressive, fulfilling the SRS criteria for studies on bracing [10]. After growth only 8% from the SpineCor sample were not progressive and 80% of the Chêneau group.…”
Section: Discussionmentioning
confidence: 99%
“…Although the ef ect of bra ce tre at ment has been ques ti o ned [4], the re is evi dence that bra ce tre at ment can stop cur va ture pro gres si on [5][6][7][8][9][10], re du ce the frequency of sur ge ry [11][12][13] and im pro ve cos me tic appearance [14][15][16]. Poor cos me tic appearance for the pa ti ent may be the most im port ant problem, which can be sol ved or at least re du ced by the use of advan ced bracing techniques in clu ding the best pos sib le cor rec tion prin ciples available to date [1,14].…”
Section: Introductionmentioning
confidence: 99%